2015
DOI: 10.1093/brain/awv011
|View full text |Cite
|
Sign up to set email alerts
|

A gradient in cortical pathology in multiple sclerosis by in vivo quantitative 7 T imaging

Abstract: We used a surface-based analysis of T2* relaxation rates at 7 T magnetic resonance imaging, which allows sampling quantitative T2* throughout the cortical width, to map in vivo the spatial distribution of intracortical pathology in multiple sclerosis. Ultra-high resolution quantitative T2* maps were obtained in 10 subjects with clinically isolated syndrome/early multiple sclerosis (≤ 3 years disease duration), 18 subjects with relapsing-remitting multiple sclerosis (≥ 4 years disease duration), 13 subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
159
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 46 publications
17
159
1
Order By: Relevance
“…Studies about histopathologic and MR imaging correlations reported increased (ie, longer) T2* in WM and cortical MS lesions, which corresponded to decreased myelin and iron content (20,21). We recently demonstrated, in a heterogeneous MS cohort, that quantitative T2* was increased at different cortical depths throughout stages of MS relative to healthy control participants, and proved to be a marker of neurologic disability more sensitive than cortical tissue loss (22).…”
Section: Patients and Study Designmentioning
confidence: 87%
See 2 more Smart Citations
“…Studies about histopathologic and MR imaging correlations reported increased (ie, longer) T2* in WM and cortical MS lesions, which corresponded to decreased myelin and iron content (20,21). We recently demonstrated, in a heterogeneous MS cohort, that quantitative T2* was increased at different cortical depths throughout stages of MS relative to healthy control participants, and proved to be a marker of neurologic disability more sensitive than cortical tissue loss (22).…”
Section: Patients and Study Designmentioning
confidence: 87%
“…Eight patients were excluded because of lack of DTI data, one patient because of the presence of tumor-like lesion, and two patients because of motion artifacts during MR imaging. Thirty-four MS patients (23 women), a subset of a previously published cohort that included 41 patients with MS (22), and included cases with clinically isolated association between WM and gray matter degeneration in MS; however, the spatial specificity of this association was not investigated (12)(13)(14)(15).…”
Section: Patients and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Steenwijk et al 9 reported a stronger relationship between cGM atrophy and WM tract pathology in RRMS compared to SPMS patients, concluding that the association between NAWM and cGM becomes increasingly independent with disease progression. The assertion that cGM and WM progression is either dependent or partly independent is supported by histopathological and radiological series demonstrating the role of meningeal mediated processes in both cortical and leucocortical lesion but not WM T2h-l development 10, 11 .…”
Section: Introductionmentioning
confidence: 93%
“…Novel pulse sequences such as double inversion recovery and phase-sensitive inversion recovery, but also higher spatial resolution, through application of ultrahigh field scanners operating at 7 T, can be used for this purpose. In this issue of Brain, Mainero and colleagues used a high-resolution T 2 *-weighted magnetic resonance sequence to examine quantitative differences across cortical layers through the use of quantitative T 2 * (the inverse of the T 2 * relaxation rate) from a multi-echo gradient-echo pulse sequence (Mainero et al, 2015). The in-plane resolution (0.25 mm) allowed the investigators to examine signal intensity and T 2 *-relaxation rates at 25%, 50% and 75% depths of the cortical mantle inward from the pial surface based on segmentation of anatomical magnetic resonance images.…”
mentioning
confidence: 99%